Sumpah Pocong and Proof in Islamic Criminal Law - Anisa, Lina Nur (JURNAL ISLAM NUSANTARA, 2024)
This article aims to analyze the sumpah pocong as a proof method within Islamic law and modern criminal law. The shroud oath is a unique cultural phenomenon in Indonesian society, especially in dispute resolution and truth verification. Although the shroud oath originates from a traditional tradition that has become part of religious practice in some communities, its validity in the formal legal system is often questioned because it does not meet the standards of proof empirically recognized in Islamic law and positive law. This research employs a library research method with a descriptive qualitative approach, exploring literature related to sumpah pocong, other methods of proof in Islamic law, and its social and legal impacts. Data were collected through a review of academic literature, accredited journal articles, and the latest factual publications, which were then analyzed using content analysis techniques. The findings indicate that sumpah pocong holds significant moral and spiritual power in specific communities. However, its validity in the formal legal system is questioned because it does not meet the empirically recognized standards of proof. Sumpah pocong is more appropriately viewed as part of local traditions that can function in customary dispute resolution. However, it cannot replace more structured methods of proof in Islamic law and positive law. In conclusion, while sumpah pocong has social relevance, its integration into the formal legal system must be cautiously used to uphold broader principles of justice.